2008
DOI: 10.1074/jbc.m802550200
|View full text |Cite
|
Sign up to set email alerts
|

Afi1p Functions as an Arf3p Polarization-specific Docking Factor for Development of Polarity

Abstract: ADP-ribosylation factors (Arfs) are highly conserved small GTPases and are critical components of vesicle trafficking. Yeast Arf3p, despite its similarity to mammalian Arf6, is not required for endocytosis but is involved in polarity development. In this study, we identified an Arf3p interacting protein 1 (Afi1p), which, through its N-terminal conserved region, specifically interacts with GTP-bound Arf3p. Afi1p is distributed asymmetrically at the plasma membrane and is required for polarized distribution of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 33 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…Yeast cells contain five structurally related Sec7 domain-containing proteins with the potential to provide GEF activity for ARF family proteins involved in vesicular transport and actin remodeling (Casanova, 2007;Anders and Jurgens, 2008;Tsai et al, 2008). Sec7p, Gea1p, Gea2p and Syt1p have been shown to be Arf1/2 GEFs and Yel1p acts as an Arf3p-GEF (Jones et al, 1999;Gillingham and Munro, 2007a;Gillingham and Munro, 2007b).…”
Section: Syt1p Regulates Golgi Localization and Activation Of Arl1pmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeast cells contain five structurally related Sec7 domain-containing proteins with the potential to provide GEF activity for ARF family proteins involved in vesicular transport and actin remodeling (Casanova, 2007;Anders and Jurgens, 2008;Tsai et al, 2008). Sec7p, Gea1p, Gea2p and Syt1p have been shown to be Arf1/2 GEFs and Yel1p acts as an Arf3p-GEF (Jones et al, 1999;Gillingham and Munro, 2007a;Gillingham and Munro, 2007b).…”
Section: Syt1p Regulates Golgi Localization and Activation Of Arl1pmentioning
confidence: 99%
“…Studies using a temperature-sensitive GEA1 or GEA2 mutant suggest that they are involved in ER-Golgi and intra-Golgi transport (Peyroche et al, 2001). Yel1p acts as a GEF for Arf3p and is involved in Arf3p-dependent actin-patch polarization (Gillingham and Munro, 2007a;Tsai et al, 2008). Syt1p acts as a GEF for Arf2p in vitro and could be involved in secretion (Jones et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…We observed that although Arf3p L23V –green fluorescent protein (GFP) and Arf3p I33V -GFP exhibited similar subcellular distributions compared with wild-type Arf3p based on microscopic observations and fractionation analysis (Supplemental Figure S2, C and D), coimmunoprecipitation analysis revealed that the interaction between Arf3p I33V and HA-Bud2p was weakened (Figure 2I). Of interest, neither L23 nor I33 of Arf3p was required for interaction with its GEF, Yel1p (Gillingham and Munro, 2007), or its polarization partner, Afi1p (Tsai et al , 2008), in yeast two-hybrid analysis (Supplemental Figure S2E). These data indicate that I33 of Arf3p specifically contributes to the Arf3p–Bud2p interaction.…”
Section: Resultsmentioning
confidence: 99%
“…To examine whether Arf3p activity could be affected by glucose depletion, we measured the amount of active Arf3p using recombinant GST-Afi1N to pull down Arf3p-GTP (Tsai et al , 2008). GST-Afi1N specifically bound to active Arf3p Q71L but not inactive Arf3p T31N (Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a GATOR1 complex, which is also composed of two DENN-related proteins (NPRL2 and NPRL3) and DEPDC5, has been reported to exhibit GAP activity toward RagA/B, even though the DENN-related domains of both NPRL2 and NPRL3 contain a u-DENN (longin) domain alone and lack c-DENN and d-DENN domains Bar-Peled et al, 2013). The yeast (Saccharomyces cerevisiae) protein Afi1p has also been identified as a DENN-related protein Levine et al, 2013a) that specifically binds GTP-bound Arf3p, but no Afi1p homologues have ever been identified in animals (Tsai et al, 2008). Based on these findings together with the fact that sequence conservation between classical DENN and DENN-related domains is very low, DENNrelated proteins are likely to function as regulators of other small GTPases, e.g., Rags and Arfs, rather than as RabGEFs.…”
Section: Rab-gefs and Their Target Rabsmentioning
confidence: 99%